Cancer registration in China and its role in cancer prevention and control - Wei, Wenqiang; Zeng, Hongmei; Zheng, Rongshou; Zhang, Siwei; An, Lan; Chen, Ru; Wang, Shaoming; Sun, Kexin; Matsuda, Tomohiro; Bray, Freddie; He, Jie (The lancet oncology, 2020)
Cancer has become a leading cause of death in China, with an increasing burden of cancer incidence and mortality observed over the past half century. Population-based cancer registries have been operating in China for about 60 years, and, in 2018, their role has expanded to include the formulation and evaluation of national cancer control programmes and the care of patients with cancer. The purpose of this Review is to provide an overview of the key milestones in the development of cancer registration in China, the current status of registry coverage and quality, and a description of the changing cancer profile in China from 1973 to 2015. This Review is a comprehensive and updated review on the development of population-based cancer registries in China over a 60-year time span. We highlight some aspects of cancer control plans that illustrate how cancer registration data have become central to the identification of health priorities for China and provide a means to track progress in cancer control for the country.